Hubungan kualitas air dengan parameter hidrologi di Sungai Batang Arau Sumatera Barat (2013-2020) - Dwi Suci Indah Permata Sari; Sigid Hariyadi; Hefni Effendi (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2021)
The Batang Arau River is the second longest river in the city of Padang (West Sumatra). Many anthropogenic activities can reduce water quality. This study aimed to determine the correlation water quality with the hydrological parameters of the Batang Arau River (2013-2020). The data taken is secondary data from several agencies in the city of Padang. Data analysed was secondary data from various institution in Padang. Simple Linear Regression between water quality parameters towards velocity and river discharge was applied. River discharge correlated with DO (r = 0.68), and velocity is very closely correlated with TDS (r = 0.82) in the rainy season. Meanwhile, very close correlation between discharge and TDS (r = 0.98) and velocity with DO (r = 0.95) in the dry season.